2011
DOI: 10.1016/j.jplph.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic response in roots of Prunus rootstocks submitted to iron chlorosis

Abstract: Iron deficiency induces several responses to iron shortage in plants. Metabolic changes occur to sustain the increased iron uptake capacity of Fe-deficient plants. We evaluated the metabolic changes of three Prunus rootstocks submitted to iron chlorosis and their different responses for tolerance using measurements of metabolites and enzymatic activities. The more tolerant rootstocks Adesoto (Prunus insititia) and GF 677 (Prunus amygdalus×Prunus persica), and the more sensitive Barrier (P. persica×Prunus david… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 42 publications
5
29
0
3
Order By: Relevance
“…(1) exogenous application of Glc, Fru, and malic acid, which are downstream metabolites of Suc and could also serve as carbon resources to provide energy, failed to have a noticeable increase in root FCR activity under Fe deficiency; (2) Fe deficiency relatively specifically increased the Suc level in roots but decreased the levels of Glc and Fru, which is consistent with the findings of Rellán-Álvarez et al (2010) and Jiménez et al (2011) in Adesoto (Prunus insititia) and Beta vulgaris plants; (3) the time-course expression of FIT, FRO2, and IRT1 correlated well with the time-course accumulation of Suc in roots during Fe-deficient treatment ( Fig. 1A; Supplemental Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(1) exogenous application of Glc, Fru, and malic acid, which are downstream metabolites of Suc and could also serve as carbon resources to provide energy, failed to have a noticeable increase in root FCR activity under Fe deficiency; (2) Fe deficiency relatively specifically increased the Suc level in roots but decreased the levels of Glc and Fru, which is consistent with the findings of Rellán-Álvarez et al (2010) and Jiménez et al (2011) in Adesoto (Prunus insititia) and Beta vulgaris plants; (3) the time-course expression of FIT, FRO2, and IRT1 correlated well with the time-course accumulation of Suc in roots during Fe-deficient treatment ( Fig. 1A; Supplemental Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, we previously suggested an auxin→NO→FIT signaling cascade in transmitting Fe deficiency information (Chen et al, 2010b), but the identity of the upstream signal of auxins remains unknown. Suc might be a promising candidate, since the amount in roots is increased by Fe deficiency (Jiménez et al, 2011;Rellán-Álvarez et al, 2010) and it often functions as an auxinlike signaling molecule involved in regulating various physiological processes (León and Sheen, 2003;Rolland et al, 2006). In addition, numerous studies have shown that Suc regulates auxin biosynthesis, transport, and metabolism (Meir et al, 1985(Meir et al, , 1989Leclere et al, 2010;Lilley et al, 2012).…”
mentioning
confidence: 99%
“…In other study using potassium bicarbonate solutions to simulate the effects of a calcareous soil, with a pH increase of 8.5, almonds showed a tolerant response, while peaches exhibited a variable response according to genotype, being 'Nemaguard' sensitive (Shi and Byrne, 1995). The root level response in tolerant rootstocks, such as 'Adesoto' reached the highest contents of organic compounds and amino acids (Jiménez et al, 2011).…”
Section: Scion-rootstock Graft Incompatibilitymentioning
confidence: 99%
“…La inducción de este enzima también se asocia con la tolerancia de distintos genotipos de Prunus a la clorosis férrica (Jiménez et al, 2011). Así mismo, es probable que la alcalinización del citoplasma asociado a la extrusión de protones puede causar la activación de la enzima PEPCasa, dando como resultado un aumento de la concentración de ácidos orgánicos para mantener el pH del citoplasma de las células de la raíz .…”
Section: Discussionunclassified
“…Por otro lado, las altas temperaturas producen la degradación de fitosideróforos, lo cual afecta directamente a la absorción del Fe en plantas de estrategia II (Bergmann, 1992 , guisante (Jelali et al, 2010a), vid (Tagliavini et al, 1995;Dell'Orto et al, 2000a;Ksouri et al, 2006), kiwi (Vizzotto et al, 1999), melocotón (Gogorcena et al, 2004;Jiménez et al, 2008Jiménez et al, , 2011 y cítricos (Treeby y Uren, 1993;Manthey et al, 1994;Pestana et al, 2005;Castle et al, 2009). …”
Section: Factores Ambientalesunclassified